'I think I had to move backwards before I could move forward again': a psychosocial case study exploring the interweaving of desistance from violent offending and professional youth worker identity formation. (1st July 2020) - Harris, Pete
Abstract : This article explores the interweaving of desistance from violent offending and professional identity formation via a psychosocial case study of a youth worker undergoing training in the UK. It follows the trainee for five years as he attempts to leave his past as a football hooligan behind him and construct a new professional identity as a youth worker. I argue that the case exemplifies how some youth professionals with lived experience of violence, if not given the time and space to build reflexive awareness, may struggle to meet the demands of professional roles such as youth work. I identify what I see as some implications for the promotion of ex-violent offenders as role models to young men involved in violence, as has recently found support within popular and political arenas in the UK. The article concludes that training and continuing professional development regimes, when designed for those with a history of violent offending, might benefit from the deep understanding of violence, professional identity formation and desistance that psychosocial analysis offers.